A New Family of Step-Up Hybrid Switched-Capacitor Integrated Multilevel Inverter Topologies With Dual Input Voltage Sources - Atif Iqbal (5504636) (2021)
In the low voltage based renewable systems like PV and Fuel cell applications, the step-up of the output voltage to drive the loads is essential. For this, the integration of switched-capacitor (SC) units with the dc-ac converters will have the potential advantages like improved efficiency, optimal switching devices, small size of passive elements (L and C) as compared with traditional two-stage conversion system (dc/dc converter and dc/ac converter). This paper focuses on a new family of step-up multilevel inverter topologies with switched capacitor integration with dual input voltage sources. With the flexibility of 2 dc sources and switching capacitor circuits, four different topologies have been suggested in this paper with features of high voltage gain, reduced component count, reduced voltage stress and self-voltage balancing of the capacitor while achieving a higher number of levels. A detailed analysis of proposed multilevel inverters has been analyzed with the symmetrical and asymmetrical mode of operations and the associated gain, the number of levels, and other performance indices are presented. An in-depth study of all the topologies has been accomplished in this paper with several comparative studies in terms of components count, voltage gain and cost. The effectiveness and practicability of the suggested topology with 13 level output voltage has been explained by the experimental results obtained from a scale down prototype. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2020.3046192